Research on the Improvement Effect of Asphalt Mixture Workability Based on Uniform Material Distribution - Ding, Gongying; Chen, Bei; Zuo, Heng; Tu, Chongzhi (Civil Engineering Journal, 2026)
Asphalt mixture workability (WAM) is critical for quality control during asphalt pavement construction. However, the methods to improve mixing quality and the impact of such improvements on material distribution uniformity remain unclear. This study aims to identify WAM enhancement strategies and explore their effects on the distribution uniformity of asphalt, aggregates, and asphalt films at the asphalt-aggregate interface. Methods include verifying the potential of mixing temperature elevation and warm mix additives (WMAs) to improve WAM, introducing three evaluation indices (asphalt distribution uniformity index ADU, aggregate distribution uniformity index HA, and asphalt film coating uniformity index AUAF), and analyzing the impacts of workability improvements on post-mixing material uniformity. Findings show that raising mixing temperature (up to 13% WAM enhancement) and adding WMAs (Sasobit boosts WAM by 10%) effectively enhance WAM; WMAs reduce the viscosity of SBS-modified asphalt during high-temperature mixing, weakening asphalt-aggregate bonding and promoting aggregate migration; higher mixing temperatures and WMAs both decrease the asphalt film coating uniformity index, with temperature exerting a more prominent effect. The innovation lies in establishing quantitative evaluation indices and revealing the intrinsic mechanism of WAM improvements on multi-dimensional material distribution uniformity, providing a theoretical basis for asphalt mixture quality optimization.